COST ACCOUNTING IN DAIRY FARMING AS A TOOL FOR EFFECTIVE MANAGEMENT - MULYK, Tetiana; DONIUK, Alona (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The work is devoted to the study of the role of cost accounting in dairy farming; defined the concept of costs in dairy production and their composition; cost objects are displayed. It was also researched that increasing the efficiency of the industry will not happen if cost management is not properly organized. The current state of cost accounting in dairy farming is analyzed: typical problems and shortcomings in the cost accounting system and factors affecting the quality of accounting information are identified. It is highlighted that the factors affecting the efficiency of accounting include internal (financial, organizational, technical) and external (normative-legal, economic, natural-climatic). The results of the study can be used to develop recommendations for improving cost accounting on dairy farms. Such effective cost management tools as: budgeting, standard costing, ABC method were studied. It was determined that cost accounting is not only a regulated procedure, but also an important element of increasing the efficiency of operation and competitiveness of the enterprise on the market. The results show that systematic cost accounting is an integral part of an enterprise’s strategy, as it allows optimizing resources, making informed management decisions, and increasing market competitiveness. The necessity of introducing modern technologies in cost accounting is also substantiated using the example of accounting automation, electronic document management system and cloud technologies. These tools not only help to optimize production processes and reduce risks, but also increase the transparency and reliability of accounting information. As a result, companies become more competitive and resilient to changes in the market environment.